IMPLEMENTASI KURIKULUM 2013 PADA MATA PELAJARAN EKONOMI DI SMA NEGERI DI KOTAPADANG (TINJAUAN RENCANA PELAKSANAAN PEMBELAJARAN) - Hanisa Hanisa; Syamwil Syamwil; Dessi Susanti (Jurnal Ecogen, 2018)
The purpose of this study is to analyze the lesson plans that have been prepared by teacher of economics. The type of this study is descriptive. The population in this study are the lesson plans that have been prepared by teachers of senior high school in Padang city that have nine lesson plans. The sample is selected by using purposive sampling technique, it is schools that have different accreditation values that location in Koto Tangah and Padang Utara. The data collected are lesson plans for 10th grade in second semester. The lesson plans analyzed by using instrument assessment of lesson plan based on the regulation of ministry education Number 22 A Year 2016. The result showed that the completeness of lesson plans that have been categorized very good. Most of lesson plans curiculum 2013 that prepared by teachers based on the regulation of ministry education Number 103 Tahun 2014 and not based on the regulation of ministry education Number 22 A Year 2016. The contents of lesson plans showed that the learning objectives, indicators, learning methods, learning media, learning resources, and learning steps have “very good” category. Learning materials and assessment have “very good” category. This showed that the contents of lesson plans that prepared by economics teachers are comformity with curriculum 2013.Keyword : Lesson Plan, Implementation of Curriculum 2013